(untitled) (Research, Society and Development, 2020)
The awareness and sensitivity of young people and adults to blood donation is very important for the preservation of human life. This work aims to clarify how simple blood donation is and demystify its taboos, myths and prejudices through literature. Through a refinement in the choice of scientific articles, 22 more applicable articles were selected for a deeper understanding of the subject, as well as searches on electronic pages of organs and entities, manuals and hematology reports. The work of raising awareness in volunteering must be carried out, breaking the myths and prejudices of the population, so that the action of solidarity prevails over fear.